Fast DNA encoding algorithm inspired by the SPOOLing system - Zhang, Xiaoqiang; Tian, Jingxi (Medical & biological engineering & computing, 2022)
The digital images are widely used in many fields, such as the military, government, and traffic. DNA encoding, as an important means of image encryption, has received increasing attention due to its powerful parallelism. But its low coding efficiency limits its application. This paper designs a quartering search method and proposes a fast DNA encoding algorithm inspired by the simultaneous peripheral operations online system. By trading off memory for time, the base combinations corresponding to 256 different pixel values are precomputed and prestored in the computer memory or hard disk in advance. When the corresponding DNA encoding or decoding operations are carried out, the data can be called to avoid a large number of repeated calculations. Experimental results and comparative analyses show that the proposed algorithm can greatly improve the efficiency of DNA encoding or decoding and be practical. Our algorithm can further facilitate the promotion and application of DNA encoding in the field of image encryption. Graphical abstract